2000
DOI: 10.1046/j.1365-2540.2000.00743.x
|View full text |Cite
|
Sign up to set email alerts
|

Contact zone between chromosomal races of Mus musculus domesticus. 2. Fertility and segregation in laboratory-reared and wild mice heterozygous for multiple Robertsonian rearrangements

Abstract: Litter size, anaphase I nondisjunction and X±Y dissociation at metaphase I were studied in homozygous and heterozygous house mice from a central Italian chromosomal hybrid zone between the CD (2n 22) race and the standard race (2n 40). We also observed the segregation of the two chromosomal forms (Robertsonian and non-Robertsonian) in male and female multiple heterozygotes from the karyotype of their ospring and chromosomal arm counts of metaphase II. Litter size was signi®cantly reduced in the F1 hybrids, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
0
7

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 28 publications
8
70
0
7
Order By: Relevance
“…Male homozygotes and single trivalentcarrying heterozygotes showed very low levels of aneuploidy and GCD in accordance with data reported for wild house mice elsewhere (Hauffe and Searle, 1998;Castiglia and Capanna, 2000). In contrast, the presence of a chain-of-four meiotic pairing configuration (that is, complex heterozygosity) reduced the reproductive performance of male hybrids, due to both a higher aneuploidy rate and spermatogenetic dysfunction.…”
Section: Fertility Estimatessupporting
confidence: 89%
See 2 more Smart Citations
“…Male homozygotes and single trivalentcarrying heterozygotes showed very low levels of aneuploidy and GCD in accordance with data reported for wild house mice elsewhere (Hauffe and Searle, 1998;Castiglia and Capanna, 2000). In contrast, the presence of a chain-of-four meiotic pairing configuration (that is, complex heterozygosity) reduced the reproductive performance of male hybrids, due to both a higher aneuploidy rate and spermatogenetic dysfunction.…”
Section: Fertility Estimatessupporting
confidence: 89%
“…Premeiotic perturbations have been also observed in some cases causing a reduction in germ cell number (Garagna et al, 1990;Hauffe and Searle, 1998;Banaszek et al, 2000;Wallace et al, 2002). Data from different mammalian species (including human) have shown that values of underdominance vary according to the nature of the rearrangement, the chromosomes concerned, the breakpoint site, the gender and also the genetic context and age (King, 1993;Searle, 1993;Djelati et al, 1997;Hauffe and Searle, 1998;Castiglia and Capanna, 2000;Wallace et al, 2002;Pellestor et al, 2005;Anton et al, 2006). Most experimental analyses of the effects of chromosomal heterozygosity on reproductive fitness stem from studies on humans, the house mouse and the common shrew.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these studies have found hybrids showing trivalents at diakinesis, with hybrid zone widths from 0.5 km (Chatti et al, 1999) to 30 km . Fertility studies show that gene flow should occur freely between races differing in only a few independent metacentrics: heterozygotes for 1-3 metacentrics have normal levels of fertility (Winking et al, 1988;Wallace et al, 1992;Castiglia and Capanna, 2000). However, if the differences between races involve many independent metacentrics the fertility of structural heterozygotes is more severely impaired (Redi and Capanna, 1988;Said et al, 1993;Castiglia and Capanna, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Fertility studies show that gene flow should occur freely between races differing in only a few independent metacentrics: heterozygotes for 1-3 metacentrics have normal levels of fertility (Winking et al, 1988;Wallace et al, 1992;Castiglia and Capanna, 2000). However, if the differences between races involve many independent metacentrics the fertility of structural heterozygotes is more severely impaired (Redi and Capanna, 1988;Said et al, 1993;Castiglia and Capanna, 2000). In these extreme cases, both gene flow and the number of hybrid individuals is expected to be low, as in the Tunisian hybrid zone between the Monastir race 2n = 22 and the standard one (Chatti et al, 1999).…”
Section: Introductionmentioning
confidence: 99%